2017
DOI: 10.1002/ca.22934
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of anatomy laboratory pedagogies

Abstract: The debate regarding anatomy laboratory teaching approaches is ongoing and controversial. To date, the literature has yielded only speculative conclusions because of general methodological weaknesses and a lack of summative empirical evidence. Through a meta-analysis, this study compared the effectiveness of instructional laboratory approaches used in anatomy education to objectively and more conclusively synthesize the existing literature. Studies published between January 1965 and December 2015 were searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
151
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(163 citation statements)
references
References 75 publications
9
151
0
3
Order By: Relevance
“…The “Smell of the dissecting room” is a negative reaction whose perception as unpleasant increases with time. Students, particularly female students, do not seem to get used to it, with figures similar to those indicated by other studies, at between 60% and 90% (Dinsmore et al, ; Leboulanger, ; Getachew, ; Mompeó Corredera, ; Wilson et al, ). Other studies, however, show considerably lower values, at around 40% (Cahill and Ettarh, ; Arora and Sharma, ; Bati et al, ; Qamar and Osama, ; Dissabandara et al, ).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The “Smell of the dissecting room” is a negative reaction whose perception as unpleasant increases with time. Students, particularly female students, do not seem to get used to it, with figures similar to those indicated by other studies, at between 60% and 90% (Dinsmore et al, ; Leboulanger, ; Getachew, ; Mompeó Corredera, ; Wilson et al, ). Other studies, however, show considerably lower values, at around 40% (Cahill and Ettarh, ; Arora and Sharma, ; Bati et al, ; Qamar and Osama, ; Dissabandara et al, ).…”
Section: Discussionsupporting
confidence: 82%
“…As well as reinforcing the theoretical aspects of their education, dissection also offers the student the opportunity to gain a better understanding of the human body. Working on a cadaver is undoubtedly a deeply emotional experience, but also one that allows students to develop the competence and coping skills that will be applied later in their professional careers (Marcos et al, ; Elizondo‐Omaña et al, ; Böckers et al, ; Van Wyk and Rennie, ; Wilson et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some schools are resistant to change because of the cost, time, and inherent risks associated with implementing new technologies. Others see no reason to stop using traditional educational approaches that have continually demonstrated efficacy [7]. For example, a meta-analysis that compared different methodologies of anatomical education showed that dissection versus prosection versus the use of digital media did not impact medical students’ academic performance [7].…”
mentioning
confidence: 99%